Morphological response and genetic variability of four species of chili pepper (Capsicum spp.) under infection of pepper yellow leaf curl virus - Tri Wahono Dyah Ayu Sayekti; MUHAMAD SYUKUR; SRI HENDRASTUTI HIDAYAT; AWANG MAHARIJAYA (Society for Indonesian Biodiversity, 2021)
Abstract. Sayekti TWDA, Syukur M, Hidayat SH, Maharijaya A. 2021. Morphological response and genetic variability of four species of chili pepper (Capsicum spp.) under infection of pepper yellow leaf curl virus. Biodiversitas 22: 4758-4765. Chili pepper has various types and species, but only five known species are commonly used and consumed. Most cultivated chili is susceptible to various plant diseases, one of which is Pepper yellow leaf curl disease (PYLCD) caused by Pepper yellow leaf curl virus (PYLCV) (Begomovirus, Geminiviridae). To control PYLCD, resistant variety assembly is required to prevent virus infection in cultivated plants. From this research, testing on four chili species is expected to provide information regarding the resistance and performance of chili peppers to conditions infected with PYLCV. This study was conducted at Dramaga Bogor, West Java, Indonesia in two experimental units: planting under virus-free conditions (as control) and virus-infected conditions. Each experimental unit was carried out using a single factor Randomized Complete Block Design (RCBD) with three replications. Twenty-nine genotypes of chili pepper were used consisted of four species, including C. annuum, C. frutescens, C. chinense, and C. baccatum. Of the 29 genotypes tested, thirteen genotypes in the resistant, nine genotypes in moderate resistant, two genotypes in moderate susceptible, three genotypes in the Susceptible, and two genotypes in the highly susceptible category. The heritability, genotypic coefficient of variance (GCOV) and phenotypic coefficient of variance (PCOV) value obtained from testing for all characters is high, ranging from 65.16-99.12%, 14.87-82.60%, and 15.77-84.45%, respectively. Most of the genotypes from C. chinense showed good resistance to PYLCV. In general, by considering the category of the resistance level and other characters such as productivity, ‘Jolokia’ (C. chinense), ‘Anies’ (C. annuum) and ‘Bonita’ (C. frutescens) can be ascertained as potential candidate sources of resistance to PYLCV.